EFFECT OF BORASSUS ACTHIOPUM EXTRACT AS A BIOLOGICAL EXTENDER ON SEMEN CHARACTERISTICS, FERTILITY AND HATCHABILITY IN CHICKEN - Adebisi, Adeyina Oluwatoba; Akanbi, Ademola Samuel; Okukpe, Kehinde Matthias; Ogbah, Odemairo Issac; Adegboye, Adiru Afolabi; Moshood, Moshood Afolabi (Journal of Agricultural Sciences (Belgrade), 2017)
Abstract: Borassus aethiopum extract as a biological extender was evaluated on semen quality, fertility and hatchability and chicken under warm preservation of 37 degree centigrade. The extenders were and 1: 5 and 1:10 (extract to normal saline) and preserved for 0, 1, 2, 3 and 4 hours respectively and a factorial design layout. There was no significant (p> 0.05) Effect of extender on semen characteristics within 2 hours of preservation. However, motility (%) significantly (p <0.05) reduced when the seed was preserved more than 2 hours. Interactions between the extender ratios and period of preservation were significant (p <0.05) for motility (%), dead and abnormal cells. Motility (%) did not differ significantly (p> 0.05) higher than 1:10 and 1: 5 and was above 70%. Using 1:10 and fertility and hatchability trial and randomized complete design layout showed that fertility decreased, 95% at 0 hour to 73.1% at 4 hours while hatchability decreased from 71.4% at 0 hour to 61.5% at 4 hours. It was concluded that Borassus aethiopum extract can be used to extend and preserve the seeds of chicken for 3 hours with good fertility and hatchability of eggs.